A Novel Enuresis Alarm for Toilet Training Students With Intellectual Disability: An Initial Evaluation in a School Setting. Issue 4 (December 2016) - Mruzek, Daniel W.; McAleavey, Stephen; Engel, Suzanne; Smith, Tristram
In this study, a novel enuresis alarm device using a miniaturized radio frequency module and disposable sensors made with inexpensive conductive ink was used to teach toilet use for urination with three participants with severe intellectual disability (two males and one female; aged 7–15 years) in a private special education school setting. At study entry, the participants did not use the toilet for urination independently, despite prior training attempts using standard behavioral interventions. For each participant, the enuresis alarm was used as part of a manualized behavior modification program. Two of the participants progressed markedly in the acquisition of toileting skills during participation in the program, but results for the third participant were less clear. Data suggest high staff satisfaction with the device and procedure and several possible advantages over standard behavioral intervention. Thus, an enuresis alarm that comprises state-of-the-art technology may be useful for teaching toileting skills in classroom settings for some individuals with developmental disabilities.